ASSESSMENT OF KNOWLEDGE, ATTITUDE, AND PRACTICE (KAP) RELATED TO ORAL HEALTH IN RESIDENTS OF THE PUSKESMAS PEGIRIAN AREA - Yessy Andriani Fauziah; Eveline Yulia Darmadi; Imelda Ritunga; Della Aulia; Dany Agus Susanto (LPPM Univ. Ibn Khaldun Bogor, 2026)
Oral and dental health remain important public health issues because they directly affect overall well-being and quality of life. Community-based Puskesmas play a crucial role in promoting preventive oral health habits within the community. This study explored levels of knowledge, attitudes, and daily practices regarding oral health among community members at Pegirian Puskesmas. A descriptive study was conducted with 50 participants who took part in an oral health education activity. The analysis revealed that most participants possessed good knowledge and held very positive attitudes toward oral health; however, these attitudes were not always reflected in their everyday practices. The primary challenge identified was the disparity between what people know and how they apply it in their daily lives. For this reason, health education was delivered with an emphasis on strengthening behaviour and providing practical guidance. The results indicated that attitudes were the strongest aspect, followed by knowledge, while oral health practices remained the weakest. In conclusion, oral health promotion efforts should not only aim to increase knowledge and improve attitudes but also place greater focus on behaviour-based approaches to achieve lasting oral health outcomes.